수상 후 발생한 요부 탈장의 PHS를 이용한 교정 - 정민(Min Chung) (Annals of surgical treatment and research, 2009)
Lumbar hernia is a rare disease. Only five papers on lumbar hernia are found in the Journal of the Korean Surgical Society. Lumbar hernia is an extrusion of intraperitoneal or extraperitoneal organs of the abdomen through a defect of the transversalis fascia or the transversus abdominis muscle aponeurosis in the posterolateral abdominal wall. The most frequent symptom of this hernia is a protruding mass at the lateral abdominal wall with increased abdominal pressure. I encountered a case of lumbar hernia. The subject fell off of a subway platform. The cervical spine was injured and he suffered from quadriplegia. After several operations, he recovered from the quadriplegia. Following that, he discovered a left lumbar mass, incidentally. CT and MRI revealed this mass to be a Grynfeltt’s hernia. This hernia was corrected by open method with PHS. There were no complications or discomfort after the operation. I report this case with a review of the literature. Lumbar hernia is a rare disease. Only five papers on lumbar hernia are found in the Journal of the Korean Surgical Society. Lumbar hernia is an extrusion of intraperitoneal or extraperitoneal organs of the abdomen through a defect of the transversalis fascia or the transversus abdominis muscle aponeurosis in the posterolateral abdominal wall. The most frequent symptom of this hernia is a protruding mass at the lateral abdominal wall with increased abdominal pressure. I encountered a case of lumbar hernia. The subject fell off of a subway platform. The cervical spine was injured and he suffered from quadriplegia. After several operations, he recovered from the quadriplegia. Following that, he discovered a left lumbar mass, incidentally. CT and MRI revealed this mass to be a Grynfeltt’s hernia. This hernia was corrected by open method with PHS. There were no complications or discomfort after the operation. I report this case with a review of the literature. KCI Citation Count: 3